Ozma of OZ - Shanower, Eric (Marvel Entertainment, 2012)
L. Frank Baum's magical world comes to life once again as out beloved Dorothy Gale takes yet another unexpected trip to a mystical, faraway land. This time Dorothy winds up in the land of Ev; she meets new friends such as Tik-Tok the mechanical man and Billina, perhaps the cleverest chicken you'll ever encounter. Dorothy will also have to face the wicked Nome King, who's imprisoned the royal family of Ev. Lucky for her, she'll get help from her Oz friends such as the Tin Woodman and the Scarecrow - along with the new Queen of Oz, the lovely Ozma! But can even their combined might win the day and see Dorothy back home?